Preservation in Digital Cartography Archiving Aspects - Jobst, Markus (Lecture Notes in Geoinformation and Cartography, 2010)
This book "Preservation in Digital Cartography: Archiving Aspects" should give an overview on how to preserve digital cartographic appli- tions and geospatial data in a sustainable way. The intention of this book is to shape the opinion of affected parties and to bring together various d- ciplines. Therefore adjacent chapters will generally deal with information technologies, Service-Oriented Architectures, cybercartography, reprod- tion and historic cartography, which all together can be subsumed in p- spective cartographic heritage. The survival of this digital cartographic heritage will base on long-term preservation strategies that make use of - tensive dissemination on the one hand and sustainable digital archiving methods on the other. This includes a massive development of paradigm that expands from "store-and-save" to "keep-it-online". The paradigm "store-and-save" is mainly used for analogue masters that consist of st- age media, like vellum, and their visible content. Avoiding the storage - dia from degeneration in climate-controlled areas will help to keep the content accessible. In the digital domain the high interdependency of st- age media, format, device and applications leads to the paradigm "keep-- online" which for example describes the migration to new storage devices. In fact this expansion of paradigm means that the digital domain calls for ongoing actions in order to preserve cartography for a long term.